Heterologous artificial fertilizaltion: another return to the matrilinear society? - Fiori, Angelo; Caprioli, Lea Cinzia (Medicina e Morale, 1994)
After a brief historical-anthropological note about thc primitive matrilinear societies, the authors describe the most important intemational laws on a reproductive technologies, concentrating on the regulations regarding the legal recognition of paternity for the partner who gave his consent for the heterologous artificial fertilization and the anonymity of the semen donor. In fact one can see the contradiction between the present possibilities of the biological research for paternity, which with genetical investigations based on the use of the polymorphisms of the blood allows anyone to know who their biological father is, and the regulations on anonymity which, since they do not allow a child to know who his real father is, create considerable inequalities among citizens. Heterologous artificial fertilization is considered to be another regression to the matrilinear society, in which the protofamily structure was concentrated on the woman, who had a dominating role as an instrument of fertility. The article then comments on the recent sentence of the Cremona Court (Italy) which granted the request of a child, born following artificial fertilization with heterologous sperm, who refused to acknowledge his patemity. Since in Italy there is no law on heterologous artificial fertilization, the Court took the only path available in the present national legal panorama, basing its sentence on Articles 231 and 235 of the Civil Law. The authors then hope that the public will reflect on the so-called "prodigies" of science and of progress, in order to avoid laws that, because of their permissiveness, makc it possible to upset human beings' true biology.